Education response to COVID 19 pandemic, a special issue proposed by UNICEF: Editorial review. (November 2021) - Reuge, Nicolas; Jenkins, Robert; Brossard, Matt; Soobrayan, Bobby; Mizunoya, Suguru; Ackers, Jim; Jones, Linda; Taulo, Wongani Grace
Abstract: This editorial paper presents 11 papers related to the special issue proposed by UNICEF on the Education Response to COVID-19. The COVID-19 pandemic provoked an education emergency of unprecedented scale. At its onset in February 2020, school closures were announced in the worst-hit countries. At the peak of the crisis, 90 per cent of learners worldwide had had their education disrupted. Some learners, especially those from the most marginalised population groups, were put at risk of permanent dropout, provoking long-term and significant negative effects on children's life-long wellbeing and the socio-economic development of their communities and countries. This special issue, which received contributions from UNICEF staff and various researchers, focuses on the impact of school closures, the effectiveness of remote learning solutions, equity implications, the mitigation of learning loss and notions around re-opening better. Different research perspectives and evidence is gathered to help strengthen policy considerations and future planning. The conclusion emphasizes building on the innovative solutions generated by the response to the crisis to make education systems more resilient, whilst also reinforcing the focus on equity and inclusion so that pre-existing disparities are not exacerbated in the future.